Analisis Hubungan Kemampuan Pemahaman Konsep IPA terhadap Keterampilan Berpikir Kritis Siswa SMP pada Materi Pesawat Sederhana - Desmauli Lumbanbatu; Nancy Susianna; Alvin Stanza Kiswandhi; Nerru Pranuta Murnaka (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the relationship between students' understanding of science concepts and their critical thinking skills in junior high school, specifically on the topic of simple machines. The research method used is descriptive correlational with a quantitative approach. The sample consisted of one class. Data were collected through tests, including a concept understanding test and a critical thinking skills test. The analysis results show a significant relationship between the understanding of science concepts and students' critical thinking skills. These findings are consistent with previous studies stating that a strong understanding of concepts can enhance students’ critical thinking abilities. Based on these results, it is recommended that science curricula integrate learning approaches that simultaneously promote conceptual understanding and critical thinking.